Problematika Pendidikan Islam Kontemporer dan Strategi Pengembangannya - Khalid Abdurrahman; Adam Maulana; Gusmaneli Gusmaneli (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
This article discusses "Contemporary Islamic Education Problems and Development Strategies," highlighting the various challenges faced by the Islamic education system in Indonesia. Issues such as value crisis, unclear educational goals, and curriculum inconsistency are the main focus of the analysis. The author emphasizes the importance of returning to the sources of Islamic teachings, such as the Qur'an and Hadith, to ensure that education is not only academically intelligent, but also rooted in moral and ethical values. In an effort to overcome these problems, educational development strategies that include curriculum innovation, improving teacher quality, and instilling spiritual values ​​are suggested. With a holistic approach, this article aims to provide guidance in a more relevant and effective Islamic education reform, which is able to produce a superior generation with noble character and is ready to face global challenges.